Treatability study for industrial wastewater by using Lateric Soil as Coagulant - Nurashikin Binti Yaacof (School of Environmental Engineering University Malaysia Perlis, 2011)
Coagulant and flocculant are the important process in the industrial wastewater treatment plant. This is because, through this process, total suspended solid and other material in the wastewater can be settle and remove. The common problem that had been usually face during the process is to remove the dyes in the wastewater. Each dye has its own chemical structure and bonding, to remove the dyes industry usually used chemical coagulant aid as the coagulant agent. There are various types of chemical coagulant aids in the industries such as Aluminium Chloride and Polyaluminium Chloride (PAC). Its capability can not be denied but the problem is chemical coagulant aid will give side effect on environment and human health.